Steganografi Citra Menggunakan Metode Least Significant Bit (LSB) dan Linear Congruential Generator (LCG) - Andre Hernandes; Hartini Hartini; Dewi Sartika (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2019)
Steganography is a method used to hide secret messages from people who are not entitled to know it. In this study the author uses one of the steganography methods, the least significant bit method (LSB) to insert bits of secret message in the form of text into digital images RGB bitmap file extension, by combining the LSB method and linear congruential generator (LCG) to generate random numbers from the position of the pixel that will be inserted a secret message. The results of this study the authors managed to build steganography applications with the Java programming language and test the quality of stego image that produces an average value Peak Signal to Noise Ratio (PSNR) that reach 51 dB. From this assessment, it was concluded that stego image produced in good quality and did not experience significant changes.